Superficial venous arrangement of the face and neck of the tufted capuchin, Cebus apella linnaeus, 1758 - Madeira, Miguel C.; Watanabe, Ii‐Sei (Wiley, 1973)
The description of the superficial veins of the face and neck was based upon the dissection of 28 male and female adult tufted or brown capuchin monkeys (Cebus apella), captured in southern Goiás, Brazil. Although the venous arrangement of these areas is basically the same in all primates, some characteristic differences were noted: 1. the anterior jugular and common facial veins were absent; 2. most specimens had a venous hyoid arch, and a connecting vessel between the external jugular and subclavian veins; 3. the inferior petrosal sinus drains into the external jugular v. through the postglenoid foramen; 4. the facial, lingual and cephalic veins open into the external jugular vein; 5. both the internal and external jugular veins have about the same diameter; 6. the vascular pattern appears to be quite stable; anatomical variations appear to be few and unimportant. Copyright © 1973 Wiley‐Liss, Inc.